PENGARUH WORK FAMILY CONFLICT TERHADAP TURNOVER INTENTION DENGAN STRES KERJA DAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada Karyawan Asri Medical Center Yogyakarta) - Erendra Bima Yudha Putra (MNJ 16 UMY 139, 2016)
This study aimed to analyze the influence of Work Family Conflict on Turnover Intention with Job Stress and Work Motivation as a mediating variable. Subjects in this study were female employees who worked at Asri Medical Center (AMC) in Yogyakarta is located in Jl. HOS Cokroaminoto 17 Yogyakarta. In this study sempel amounted to 46 respondents selected by using purposive sampling method. The analysis tool used is Path Analysis with Regression. Based on the analysis that has been done shows that Work Family Conflict significantly affect Turnover Intention, Job Stress and Work Motivation significantly influences mediate Work Family Conflict on Turnover Intention. Keywords: Work Family Conflict, Turnover Intention, Job Stress, and Work Motivation.